Peningkatan Kesadaran Digital melalui Sosialisasi Dampak Penggunaan Gadget Dan Pengelolaan Pojok Baca Di Desa Dewasari - Dewi, Uci Triyanti; Mardiana, Gina; Suryadi, Suryadi; Endah, Kiki (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2024)
The widespread use of gadgets in the digital era has had positive and negative impacts on society, especially the younger generation. In Adultari Village, residents are concerned about the negative impacts of excessive use of gadgets. Therefore, this Community Service activity aims to increase digital awareness through socializing the impact of using gadgets in the digital era and managing reading corners as alternative activities that are more positive for the community. The methods used in this activity include observation, interviews, and identifying problems faced related to gadget use. The results of this activity include education and evaluation carried out through question and answer sessions during socialization with measurements based on audience understanding. It is hoped that with the reading corner, people, especially children and teenagers, can use gadgets wisely and utilize technology for more productive activities. This activity aims to form a generation that is more critical, knowledgeable and wise in facing challenges in the digital era.